(3GdYbO GdefXe ddMcGe ajeG jLQj Hjf CjOjge ef GdYbhO hGdCMcGes - (3CHh YHO Gddg Hf YHO Gddg Hf Ydj Hf Sdehf GdcfGfjs
(3ChdgG (B:s
(3hHYO aEfg deG cGfJ GdCOdI GdTQYjI dgG eMd cHjQ ef GdOjf s
(3BNQgG (B:s
(3JeJ HMeO Gddg hMSf Yhfg hUdi Gddg Ydi fHjfG eMeO hBdg hUMHg hSde JSdjeG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B111s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 409) s
Keywords: (3Gdabg GdeGdcjs